Self-efficacy Among Older Adults in Fereydunshahr City - Morteza Aslani; Maryam Amidi Mazaheri; Marziye Batavani (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Self-efficacy is a very important factor as far as old age is concerned. Because of the numerous physical and physiological changes occurring in elder’s bodies, self-efficacy has  initiated a broad discussion among experts. Numerous studies have revealed that self-efficacy is one of the most important predictors of health behaviors among the elderly and adults in general. Keeping these facts in mind, this study was conducted to evaluate the self-efficacy among the elderly in Fereydunshahr City.  Methods & Materials The present study was a descriptive-analytical one and was conducted by means of a cross-sectional survey. Two hundred elderly people in Fereydunshahr City were selected by the systematic randomly sampling method. The average (SD) age of the elderly was 68.02 (3.7) years, and 101 (50.5%) of them were women, and 99 (49.5%) were men. The data were collected with a couple of questionnaires. The first questionnaire included demographic characteristics of the elderly, and the second was the Scherer self-efficacy questionnaire. Data were analyzed by SPSS (ver. 20) through descriptive statistics, Pearson correlation, Spearman test, and Independent t test. Results The mean (SD) score of self-efficacy among elderly was 26.6 (6.8); the independent t test showed that the self-efficacy score in those with chronic diseases was significantly lower than healthy elders. The average score of self-efficacy in the elderly who lived with family was significantly higher than those who lived alone, and the average self-efficacy score in the elderly people with jobs was significantly higher than those who were unemployed.  Conclusion Given that self-efficacy is an important component of lifestyle changes, it can be effective in changing behaviors or help in the initiating of healthy behaviors. In this study, self-efficacy of the elderly was moderate. Therefore, designing and implementing educational interventions and promoting healthy practices are recommended.